Decolonizing Possession: A Blueprint to Invisible Worlds - Glazier, Jacob; Robinson, Taylor (Journal of Scientific Exploration, 2025)
The experience of being possessed by an invisible and outside spirit seems archaic and outdated to many people today. However, the scientific and medical field of psychiatry contains diagnoses that classify this experience as a form of psychopathology, most notably Dissociative Identity Disorder (DID). Moreover, indigenous peoples and researchers have detailed many accounts of how the experience of possession makes sense within their cultural and local backdrop. In this essay, we employ the strategy of decolonization to demonstrate how psychiatry continues to exert colonial power to manage cases of possession. In so doing, we argue that psychiatry lacks a robust phenomenological and culturally sensitive understanding of spirituality. We also put forward an animistic framework more congruent with the possession experience by examining the influence of invisible worlds.